The ADAM-pelvis phantom—an anthropomorphic, deformable and multimodal phantom for MRgRT. (11th February 2019) - Niebuhr, N I; Johnen, W; Echner, G; Runz, A; Bach, M; Stoll, M; Giske, K; Greilich, S; Pfaffenberger, A
Abstract: Applicability and accuracy of the rapidly developing tools and workflows for image-guided radiotherapy need to be validated under realistic treatment-like conditions. We present the construction of the ADAM-pelvis phantom, an anthropomorphic, deformable and multimodal (CT and MRI) phantom of the male pelvis. The phantom covers patient-like uncertainties in image-guided radiotherapy workflows including imaging artifacts for the special case of the human anatomy as well as organ motion. Principles and methods were further improved from previous work. The phantom includes surrogates for muscle tissue, adipose, inner and outer bone, as well as deformable silicone organs. Anthropomorphic shapes are realized with 3D-printing techniques for the bone and the construction of the hollow silicone organ shells. Organs are constructed from patient image segmentation and further guided by reported deformation models. Imaging markers and pockets for dosimeters are included in the organ shells. The improved phantom surrogates match imaging characteristics in MRI (T1 and T2 relaxation time) and CT (Hounsfield units) of human tissues. The surrogates are suited for long term use (several months) of the phantom. Previously reported artifacts of the muscle surrogate were avoided by improved composition of the used agarose gel. Interfractional organ motion is successfully realized for the water filled bladder and the air filled rectum and showed to be reproducible with deviation below 1 mm. Volume variations of both induce displacement, rotation and deformation of the prostate. We present solutions for the construction of an anthropomorphic phantom suitable for MRI and CT imaging including deformable organs. The developed concepts of phantom surrogates and construction techniques were successfully applied in building the ADAM-pelvis phantom and can as well be adopted for other anthropomorphic phantoms. The presented phantom allows for the systematic and controlled investigation of image-guided radiotherapy workflows in presence of organ motion.